Historical dictionary of the Mongol world empire - Buell, Paul D. (Historical dictionaries of ancient civilizations and historical eras, 2003)
This Dictionary, the first work of its kind written in English, examines the history of the Mongol Empire, the pre-imperial era of Mongolian history that preceded it, and the various Mongol successor states that continued to dominate Eurasia long after the breakdown of Mongol unity